Optical output buffered ATM switch prototype based on FRONTIERNET architecture. - Yamada, Y.
We constructed a rack-mounted prototype photonic ATM switch based on the FRONTIERNET architecture. The advantages of the architecture are that its output-buffering scheme overcomes the bottlenecks that can occur when receiving and storing concurrent high-speed cells, and that there is no need to deal with contention resolution between input highways. The prototype has 16 input/output ports and 2.5 Gb/s transmission speed. Actually, six input ports and one output port are mounted in two racks. We demonstrated successful cell routing and buffering, and its stable operation, with 24-h bit-error-free switching operation. We also discussed problems to be solved in increasing the throughput of FRONTIERNET
Keywords: 2.5 Gbit/s.; FRONTIERNET architecture; Bit-error-free switching operation; Cell buffering; Cell routing; Concurrent high-speed cells; Input/output ports; Optical output buffered ATM switch prototype; Rack-mounted prototype photonic ATM switch; Throughput; Transmission speed